Why do state-owned utilities become subject to financial logics? The case of energy distribution in Flanders - Deruytter, Laura; Juwet, Griet; Bassens, David (Competition & change, 2022)
According to political economists, the state’s governance of infrastructure is becoming prone to processes of financialization. To date, however, research on how state owners of infrastructure enable and react to the entry of financial logics into such domains remains limited. This paper mobilizes the case of Eandis, a Flemish energy grid company, as a typical case to examine the causal mechanisms involved when state-owned utilities become subject to financial logics. During the 2000s, Flemish municipalities increased their ownership of Eandis, while the company deepened its debt exposure to optimize return on capital. In 2016, Eandis aimed to attract private financial equity and selected a Chinese investment fund as a potential co-shareholder. Although this buy-in was blocked, the conditions under which the state-owned company became increasingly entangled with financial markets remain unchanged and warrant a deeper examination. To explain this trajectory, we identify two causal mechanisms in the fields of market-making and ownership strategies by the multiscalar state. First, we show how regulatory models caused Eandis to focus on financial metrics such as credit ratings, subjecting management to financial market disciplines. Second, we find that budgetary constraints, combined with top-down utility governance, have made municipalities dependent on financial returns on utilities. The interaction between market-making and financial ownership strategies institutionalizes a financialized gridlock, in which municipal shareholders’ interests conflict with the need for low consumer fees and green grid investment. We argue that reforming the regulatory framework and strengthening fiscal solidarity across state layers would allow states to develop non-financialized strategies.